Observations of Ice Nucleating Particles Over Southern Ocean Waters. Issue 21 (5th November 2018) - McCluskey, C. S.; Hill, T. C. J.; Humphries, R. S.; Rauker, A. M.; Moreau, S.; Strutton, P. G.; Chambers, S. D.; Williams, A. G.; McRobert, I.; Ward, J.; Keywood, M. D.; Harnwell, J.; et al.
Abstract: A likely important feature of the poorly understood aerosol‐cloud interactions over the Southern Ocean (SO) is the dominant role of sea spray aerosol, versus terrestrial aerosol. Ice nucleating particles (INPs), or particles required for heterogeneous ice nucleation, present over the SO have not been studied in several decades. In this study, boundary layer aerosol properties and immersion freezing INP number concentrations ( n INPs ) were measured during a ship campaign that occurred south of Australia (down to 53°S) in March–April 2016. Ocean surface chlorophyll a concentrations ranged from 0.11 to 1.77 mg/m 3, and n INPs were a factor of 100 lower than historical surveys, ranging from 0.38 to 4.6 m −3 at −20 °C. The INP population included organic heat‐stable material, with contributions from heat‐labile material. Lower INP source potentials of SO seawater samples compared to Arctic seawater were consistent with lower ice nucleating site densities in this study compared to north Atlantic air masses. Plain Language Summary: The Southern Ocean is known for a prevalence of clouds that contain both liquid and ice, which are one of the most poorly understood cloud regimes in the climate system. A large gap in understanding important processes in these clouds is a lack of knowledge regarding particles (e.g., sea spray) required for forming ice crystals, termed ice nucleating particles. In a ship‐based monthlong field study, several instruments were deployed in efforts to characterize the ice nucleating particles present over the Southern Ocean for the first time in over four decades. Abundances of ice nucleating particles throughout the voyage were extremely low compared to other ocean regions, and concentrations were 2 orders of magnitude lower than the most recent survey conducted in the 1970s. We report that the ocean‐derived ice nucleating particles observed in this study were organic in nature, supporting a hypothesized link between ice nucleating particles and organic particles associated with phytoplankton blooms. The data from this study provide a desperately needed benchmark for constraining the number of ice crystals that may form in the remote and poorly understood clouds occurring over the Southern Ocean. Key Points: Number concentrations of ice nucleating particles over the Southern Ocean in March 2016 were a factor of 100 lower than historical surveys The ice nucleating particle source strength of Southern Ocean seawater was lower than previous measurements in northern hemisphere seawater Ice nucleation site densities were lower over the Southern Ocean compared to measurements of pristine air masses from other ocean basins